The Names of Cheese in the Dialects of the Georgian Language - Putkaradze, Iamze (Actual Problems of Kartvelology, 2019)
The article discusses the names of cheese in Georgian dialects. Dairy farming is characterized by significant achievements for Georgian life, which can be explained by the high technology and technology of dairy production. The type of cheese and the vocabulary associated with it are various and interesting. The vocabulary of the names of cheese in Georgian dialects is rich in both archaic and innovative forms, which form synonyms, and, therefore, they are a real treasure of the rich vocabulary of the Georgian literary language, which can occupy a legal place instead of barbarisms derived from other languages. The geography of their distribution will provide interesting material for those wishing to compile a Kartvelian dialectological atlas. The shared vocabulary of most of the geographically distant Georgian dialects, or the Georgian General Dictionary Fund, includes the following words: 1. Fully identical common Kartvelian vocabulary; 2. Relatively late vocabulary; 3. The synonyms of the word cheese; 4. The vocabulary of the same composition, but different with its meaning.